A study on knowledge of anganwadi workers about integrated child development services at three urban health centers - Baliga, Sulakshana Shridhar; Walvekar, Padmaja R. (International Journal Of Community Medicine And Public Health, 2017)
Background: Most of the studies have been concentrated on the nutritional and health status of the beneficiaries of ICDS. Less focus has been shifted over to assess the knowledge and awareness among AWW regarding recommended ICDS programmes, who are actually the main resource person. Methods: A cross-sectional study was undertaken among 76 anganwadi workers from all 76 anganwadi’s under the three urban health centers. For Anganwadi workers’ knowledge assessment, a scoring system was developed. The knowledge assessment score from each A WW was calculated based on the responses to a questionnaire containing 30 questions. Results: 88.16% of anganawadi workers had better knowledge on immunization and supplementary nutrition and only 45.39% of them had knowledge regarding referral services. No relationship was found between the educationalof the worker and her knowledge about different services provided by her (p=0.660). Conclusions: Out of total 18 (23.7%) of AWWs had poor knowledge of health services provided, 20 (26.3%) had average knowledge and 38 (50%) had good knowledge. The knowledge had no relation with experience and their educational qualification. This difference was not found to be statistically significant.